1993
DOI: 10.1016/0010-2180(93)90132-m
|View full text |Cite
|
Sign up to set email alerts
|

Flame spread in laminar mixing layers: The triple flame

Abstract: In the present paper we investigate flame spread in laminar mixing layers both experimentally and numerically. First, a burner has been designed and built such that stationary triple flames can be stabilised in a coflowing stream with well defined linear concentration gradients and well defined uniform flow velocity at the inlet to the combustion chamber. The burner itself as well as first experimental results obtained with it are presented. Second, a theoretical model is formulated for analysis of triple flam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
88
2
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(104 citation statements)
references
References 9 publications
8
88
2
6
Order By: Relevance
“…Ref. [3] is mostly significant for its modeling contribution and essentially repeated the same type of experiments of Ref. [4], albeit in a vertical configuration.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ref. [3] is mostly significant for its modeling contribution and essentially repeated the same type of experiments of Ref. [4], albeit in a vertical configuration.…”
Section: Introductionmentioning
confidence: 93%
“…Such flames are referred to as triple flames and are characterized by positive laminar flame speeds, that is, they propagate toward the unburned mixture. In the extinction mode, the edge flames present a simple edge without any tribrachial nature, that recedes away from the unburned mixture with negative flame speed [3].…”
Section: Introductionmentioning
confidence: 99%
“…Liñ án [8] and Kioni et al [9] have shown theoretically that in laminar flows, lifted flames are stabilized by a triple-flame configuration. Veynante et al [10] and Favier and Vervisch [11] have demonstrated that triple flames are able to survive strong interactions with vortices by adjusting their structure to a new transient environment, thus being more robust than pure diffusion flames.…”
Section: Introductionmentioning
confidence: 99%
“…(3) has not been addressed yet. It has been noted in the past studies that the mixture stratification in the transverse direction yields triple flames (Kioni et al, 1993;Ruetsch et al, 1995;Plessing et al, 1998). Also, the behaviour and contributions of these additional terms in the presence of significant flame curvature, complex chemical kinetics, differential diffusion effects and a wide range of local flow and mixture conditions are not investigated yet.…”
Section: Introductionmentioning
confidence: 99%